Decoding Figurative Languages Found in the Selected Songs’ Lyrics of Billie Eilish’s Hit Me Hard and Soft Album (e-Journal of Linguistics, 2025)
This study investigated the types and functions of figurative languages found in the lyrics of selected songs from Billie Eilish's Hit Me Hard and Soft (2024) album. Employing a mixed-methods approach with an explanatory-sequential design, the study identified and analyzed 232 instances of figurative expressions. The entire analysis was guided by Kennedy’s (2019) framework, which categorized figurative language into comparative, correlative, and contradictory forms. The findings revealed that metaphor was the most frequently employed comparative device, effectively conveying abstract and complex ideas, followed by simile and personification. Correlative expressions, such as metonymy and synecdoche, occurred less frequently, whereas contradictory expressions, including hyperbole, paradox, and irony, significantly contributed to emphasis and emotional depth. These rhetorical strategies enhanced the expressive quality of the lyrics, enabling nuanced emotional and symbolic interpretations. Besides, this study also underscored the critical role of figurative language in songwriting as a mechanism for bridging literal and symbolic meanings, thereby enriching audience engagement through the interplay of language, music, and performance.